Fabrication of flexible graphene paper and its electrochemical properties used in lithium ion batteries. Issue 3 (10th June 2014) - Liu, Xiaowen; Zhao, Huang; Huang, Xuemei; Hu, Yuehua; Gao, Haiqing; Liu, Xiaoxu; Shen, Lingyan
Abstract : Recent studies have shown that graphene paper (GP) is a promising candidate for novel applications in energy storage systems such as electrical batteries and supercapacitors. In this study, a low-cost and free-standing GP was produced by graphene oxide paper (GOP) in the thermal reduction method which heated GOP slowly to 500 °C in a special fixture. In the process of reduction, oxygen functional groups were decomposed and graphene oxide (GO) sheets were reduced to grapene sheets. Moreover, the smooth paper-like structure was maintained by the protection of the special fixture during the heat treatment. The GP paper showed good electrochemical property. The electrical conductivity of the GP reached 182 S cm −1 after the decomposition of oxygen functional groups. The GP as binder-free anodes of lithium ion batteries afforded a capacity of 576 mAh g −1 with good cycling stability.